Pravastatin Improves Glucose Regulation and Biocompatibility of Agarose Encapsulated Porcine Islets following Transplantation into Pancreatectomized Dogs - Lawrence S. Gazda; Horatiu V. Vinerean; Melissa A. Laramore; Richard D. Hall; Joseph W. Carraway; Barry H. Smith (Journal of Diabetes Research)
The encapsulation of porcine islets is an attractive methodology for the treatment of Type I diabetes. In the current study, the use of pravastatin as a mild anti-inflammatory agent was investigated in pancreatectomized diabetic canines transplanted with porcine islets encapsulated in agarose-agarose macrobeads and given 80 mg/day of pravastatin (n=3) while control animals did not receive pravastatin (n=3). Control animals reached preimplant insulin requirements on days 18, 19, and 32. Pravastatin-treated animals reached preimplant insulin requirements on days 22, 27, and 50. Two animals from each group received a second macrobead implant: control animals remained insulin-free for 15 and 21 days (AUC = 3003 and 5078 mg/dL/24 hr days 1 to 15) and reached preimplant insulin requirements on days 62 and 131. Pravastatin treated animals remained insulin-free for 21 and 34 days (AUC = 1559 and 1903 mg/dL/24 hr days 1 to 15) and reached preimplant insulin requirements on days 38 and 192. Total incidence (83.3% versus 64.3%) and total severity (22.7 versus 18.3) of inflammation on tissue surfaces were higher in the control group at necropsy. These findings support pravastatin therapy in conjunction with the transplantation of encapsulated xenogeneic islets for the treatment of diabetes mellitus.